Dunning Kruger Effect Pada Mahasiswa Akuntansi Di Kota Ambon - Leiwakabessy, Theophilia F.F; Limba, Franco B.; Risakotta, Kathleen A. (SEIKO : Journal of Management & Business, 2023)
This research aims to examine the cognitive bias of students' understanding of accounting through the Dunning-Kruger Effect. This research is experimental research with a True Experimental design and involves two variables, namely subjective ability and objective ability on students' understanding of accounting. The population in this study were accounting students from the Faculty of Economics and Business, Pattimura University. The sample in this study was 180 students using a purposive sampling technique. subjective ability using a questionnaire instrument consisting of 25 question items. Meanwhile, Objective Ability uses the results of the Basic Accounting test from Journaling to Preparing Financial Reports. The data analysis technique used a comparison of the Average Subjective and Objective Ability Values to see the Dunning-Kruger Effect and the Pearson Correlation Test to see the relationship between the two variables. The research results show that there is a correlation between Subjective Ability and Objective Ability in Students' Accounting Understanding and the Dunning Kruger effect occurs in 4 experimental groups based on the Grade Point Average (GPA/IPK). Keywords: Dunning-Kruger Effect, Understanding Of Accounting, Subjective Ability, Objective Ability